Emerging Socialities in 21st Century Healthcare - Hadolt, Bernhard; Hardon, Anita (Amsterdam University Press, 2017)
The landscape of health care is changing rapidly, both on an organizational and a technological level. This book gathers medical anthropologists to examine the ways that both patients and health care workers are being affected by new policies, market, and technologies. Contributors cover a wide range of topics, including vaccination, disability, migration, and self-medication, making clear that not only are changing circumstances leading to the emergence of new socialities, but they are also driving new ethics and moralities.